Assessing Record Management Practices: A Study of Compliance and Diversity - Istilamah; Hasanah, Nushrotul; Maslahah, Khoirul (Program Studi Ilmu Perpustakaan UIN Alauddin, 2023)
This research investigates the implementation of records management practices at five Islamic State Universities and Colleges (PTKINs) located in Central Java and Yogyakarta, utilizing a qualitative research approach. The examination reveals considerable diversity in records management practices across the five PTKINs. This variation can be attributed to disparities in the interpretation of policies by each institutional stakeholder regarding the significance of effective and systematic records management. The divergent policies in place also influence the support systems available. The primary differentiator among these institutions lies in their instruments, serving as the foundational framework for handling records. Following the record management model, specifically ANRI Head Regulation Number 24 of 2011, which provides guidelines for organizing records in higher education, two of the studied PTKINs, namely IAIN Kudus and UIN Walisongo, have fully implemented the four pillars outlined in the regulation. However, persisting challenges stem from a limited comprehension of records management among the human resources involved, emphasizing a critical aspect that requires focused attention.